Aspectos comportamentais de um peixe neotropical que experimenta a ausência de peixes predadores sob a perspectiva da hipótese da ingenuidade ecológica - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Populations isolated for many generations tend to develop genotypic and phenotypic changes that may increase over time and make crossing with individuals from the parent population unfeasible. This evolutionary phenomenon is known as allopatric speciation and, although relatively common, it is a slow process whose establishment is difficult to perceive in natural populations. Among the phenotypic expressions affected by isolation, behavior may show slight changes. Within this context, we investigated a population of a small Neotropical characid (Astyanax aff. fasciatus) that lives geographically isolated and completely abstaining from interactions with other fish species, and therefore experiences reduction of predation effects. Such high-level isolation configuration is rare in nature and provides an excellent opportunity to test ecological-evolutionary hypotheses, such as the Naïveté Hypothesis (NH), which suggests that isolation between prey and predator leads to the loss of the prey's ability to recognize or respond efficiently to a threat of predation. In this scenario, we experimentally tested (i) predator recognition (NH, level 1), under the hypothesis that individuals from isolated populations (IP) lost their ability to recognize a predatory fish; and (ii) the response to a predation cue (NH, level 2), under the hypothesis that these individuals present an anti-predator response which is similar to those presented by individuals from the non-isolated population (NIP). The results suggest that individuals in IP have a decreased perception of the threat of specific predation, but their response to the generalized attack cue is similar to the response presented by individuals in the NIP. These results suggest that the absence of a given predator over generations led to the loss of high-costly behaviors (such as vigilance), and subsequently lower cost behaviors (such as escape). In addition, the scape agility is probably not diminished as these populations are subject to stimuli from other predators (such as birds) and to negative intraspecific interactions, such as aggressiveness in the dispute over resources.
Keywords: evolução; naïveté; peixe; população isolada; predação; Evolution; naïveté; fish; isolate populations; predation; CNPQ::CIENCIAS BIOLOGICAS